Giant fibro epithelial polyp in a young girl: A rare case report. (2017) - Kumar, Anil; Hasin, Nadia; Sinha, Amit Kumar; Kumar, Subhash; Bhadani, Punam
Highlights: Giant Fibro epithelial Polyp (FEP) is a very rare benign neoplasm. FEP is usually occurs in reproductive age group of female (Usually after 4th decade of life). It's very rare to find the FEP of more than 5 cm in diameter.s. Excisional biopsy is the best way to confirm the diagnosis. Abstract: Introduction: Fibro epithelial Polyp (FEP) is a polypoid outgrowth of epidermis and dermal fibro vascular tissue. This polyp is most commonly found in oral cavity, neck and axilla, though any skin fold may be affected like groin. These polyps are usually less than 5 cm in size and rarely occur before 4th decade of life. Excision is the treatment of choice for such lesion. Presentation of case: A 20 year old female patient presented with a large pedunculated mass originating from the left groin area extending up to the left knee joint. It measured 42 cm in diameter. Surgical excision with primary closure was performed. We present this case because of its size and its occurrence at early age. Discussion: In this case, a mass of 42 × 22 × 10 cm in a 20 years female has been described. This mass was diagnosed as a giant FEP, which is the largest size FEP reported, to the best of our knowledge. FEP usually occurs in females of reproductive age group but in the present case it occurred in a 20 years old female. Various other lesions like leiomyomas, superficial angiomyxoma and neurofibroma mimic FEP. Complete excision with long term follow-up is the best option in such patient. Conclusion: Giant FEP is a benign lesion, sometimes it may be misdiagnosed as malignant lesion because of its larger size and occurrence in early age. Hence excisional biopsy is important to confirm the diagnosis.